1995
DOI: 10.1007/bf00311527
|View full text |Cite
|
Sign up to set email alerts
|

Effect of granulocyte colony-stimulating factor (G-CSF) on chemotherapy-induced oral mucositis

Abstract: In this study, the ability of granulocyte colony-stimulating factor (G-CSF) to treat or prevent chemotherapy-induced oral mucositis in patients with advanced breast cancer was evaluated. A total of 14 patients who received intraarterial (i.a.) adriamycin (ADM) preoperatively were divided into two groups according to whether or not G-CSF was given. Thus, group A (n = 7) was given G-CSF and group B (n = 7) was not. G-CSF therapy reduced both the incidence and duration of ADM-induced oral mucositis, and a positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
1
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 27 publications
0
18
1
1
Order By: Relevance
“…We did not change our previous conclusion that no guideline was possible because of insufficient evidence. The panel concluded that no guideline could be provided for or against the use of subcutaneous G-CSF for the prevention of mucositis in patients treated with CT since studies reported conflicting results [48,49]. Crawford et al [50] reported a beneficial effect, whereas a randomized controlled trial by Patte et al [51] found that G-CSF was not effective to prevent mucositis in this setting (Table 1).…”
Section: Granulocyte Colony-stimulating Factormentioning
confidence: 99%
“…We did not change our previous conclusion that no guideline was possible because of insufficient evidence. The panel concluded that no guideline could be provided for or against the use of subcutaneous G-CSF for the prevention of mucositis in patients treated with CT since studies reported conflicting results [48,49]. Crawford et al [50] reported a beneficial effect, whereas a randomized controlled trial by Patte et al [51] found that G-CSF was not effective to prevent mucositis in this setting (Table 1).…”
Section: Granulocyte Colony-stimulating Factormentioning
confidence: 99%
“…Laboratory studies have shown however, that G-/GM-CSF influence proliferation and migration of non-haematopoietic cells, including endothelial cells 118 and keratinocytes, 119 suggesting that they may act as regulatory signals outside the haematopoietic system. Clinical studies using subcutaneous G-CSF or GM-CSF have shown a beneficial effect on oral mucositis 110,[120][121][122][123][124][125][126] (Table 3). In addition to the amelioration of severe and long-lasting neutropenia, systemic G-CSF or GM-CSF activates neutrophil migration, chemotaxis, phagocytosis and cytotoxicity.…”
Section: G-/gm-csfmentioning
confidence: 99%
“…There was a significant reduction in both grade 3 and 4 mucositis and infection in the GM-CSF-treated arm (Nemunaitis et al, 1995). A Japanese study (Katano et al, 1995) of only 14 patients receiving intra-arterial doxorubicin with or without G-CSF suggested that oral mucositis secondary to doxorubicin can be reduced or prevented by this cytokine.…”
Section: Granulocyte and Granulocyte Macrophage Colony-stimulating Famentioning
confidence: 99%